PENGARUH PEMBERIAN KOMPOS DAUN GAMBIR (Uncaria gambir Roxb.) TERHADAP PERTUMBUHAN DAN HASIL TANAMAN JAGUNG (Zea mays L.) - Verawati, Yuli - (Pendidikan Biologi, 2014)
Corn (Zea mays L.) is a monoecious plant (monoceous), male flowers and female flowers are in one tree, which belong to the family Poaceae (Gramineae). Corn crop is one of the important food crops, in addition to wheat and rice. Low productivity and quality of maize due to less intensive farming techniques, fertilization and care. Fertilization with compost is one option the current trends. For research that has been conducted in July through September 2013 held at the District Barung-Barung Belantai Koto XI Tarusan South Coastal District in order to know the effect of leaf compost gambier (Uncaria gambir Roxb.) On the growth and yield of crops of corn (Zea mays L.) This research is an experiment, with a completely randomized design (RAL) consisting of 5 treatments and 5 replications. The treatment is administration of leaf compost gambier / polybag. Treatment B (200 grams), C (400 grams), D (600 grams), E (800 grams) and A (0 grams) as a control. Observations were observed is the number of leaves, plant height, stem diameter, ear length, cob diameter. Data were analyzed using analysis of variance and LSD test continued at Î± level of 5%. Research results when analyzed with analysis of variance showed that the use of leaf compost gambier (Uncaria gambir Roxb.) Did not affect the number of leaves, cob length, cob diameter but different from the stem height and stem diameter. In cultivating corn plants using compost leaves is recommended because it is more ekonomois gambier and environmentally friendly.